Creation and Elevation of Pot Rests: Southerners’ Local Wisdom to Decorative Products of Khanap Nak Sub-District, Nakhon Si Thammarat Province - Kritsanaphan, Prachya; Jitpakdee, Rungrawee (Area Based Development Research Journal, 2020)
The basketwork of pot rests, one of the local wisdom examples in Khanap Nak sub-district, Nakhon Si Thammarat province, is gradually disappearing from the area. The research objectives are to design and develop products by using the basketwork technique of pot rests and to upgrade such products to become decorative products with the identity of the community. The tripartite participatory action research with an area-based approach has engaged nine researchers and basketwork masters in the community and three boutique hotel entrepreneurs. The following processes ensued 1) Tripartite demand analysis; 2) Product design; 3) Product forming tests and basketwork technique development; 4) Product development; and 5) Marketing and consumer satisfaction. The actions taken have given the basketwork product the community identity. The decorative products’ design concept concerns the lifestyle of nipa palm forest dwellers, nipa palm elements, the chimney of ancient rice mills, local house styles, and water birds in nipa palm forests. The developed decorative products are classified into two main categories, including lighting products and decorative products with eight product works in total. The pot rest’s new basketwork technique has drawn attraction to the products and raised the value by sixteen times, generating more income for the community. Additionally, the community has jointly established a self-managed, holistic nipa palm ecosystem learning centre at Bang Talumphor village to encourage the community to develop and utilize resources from the nipa palm forest to create new products that get into the market.